Judicial Review of Insurance Ombudsman Decisions: A Legal Perspective (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In this research, we set out to comprehend the ombudsman idea and find the problems with its implementation by conducting a thorough examination of its history, development, and operation in various regions of the globe. In light of the foregoing and in light of international precedents for ombudsman schemes, the following recommendations are put forth: (i) the establishment of a unified regulatory body overseeing all state lokayukts to standardize their respective jurisdictions and the means by which complaints are addressed; (ii) the transmission of technical circulars from insurance companies to the Ombudsman's office; and (iii) the regular updating of annual reports on complaints filed and resolved in the online platforms of electricity ombudsman, Lokpal, and other ombudsman; and (iii) the modification of appeal provisions in other types of ombudsman, similar to that of the Banking Ombudsman. A step forward towards good governance may be achieved by using extracts from this research to elevate the position of ombudsman among the Indian populace, since it offers a comprehensive and well-organized review of all the many facets of the position.